The Philosophy of Morality and Law Enforcement in Corruption: A Case Study of State Losses of IDR 271 Trillion - Aldi Alfarel Sinulingga; Indana Sephia Citra; Saif Arrasid; Indra Utama Tanjung (ISNU Nine-Star Multidisciplinary Journal, 2025)
Corruption in Indonesia is a serious problem that has damaged the country's social and economic structures. One significant case is corruption that caused state losses of up to Rp 271 trillion. In this regard, the application of the law to perpetrators of corruption is important to examine from a moral philosophy perspective. This article examines the 6.5-year prison sentence imposed on the perpetrator who caused this significant loss, using deontological and utilitarian ethical perspectives. Is this sentence sufficient to provide a deterrent effect and satisfy society's sense of justice? Or does it ignore the serious impact of corruption? This article aims to explore the role of the legal system in upholding justice and how moral philosophy can provide insight into existing legal policies. Furthermore, this research also examines the potential for improving the legal system to be more effective in handling major corruption cases for the sake of more meaningful justice for society and the state.